1994
DOI: 10.1136/jnnp.57.7.778
|View full text |Cite
|
Sign up to set email alerts
|

Pure motor demyelinating neuropathy: deterioration after steroid treatment and improvement with intravenous immunoglobulin.

Abstract: Within one month of starting oral prednisolone treatment weakness unexpectedly increased in four patients aged 34 to 75 years with purely motor forms of acquired chronic demyelinating neuropathy. By contrast, steroids produced the expected improvement in 11 other patients with symmetric sensorimotor chronic inflammatory demyelinating polyneuropathy. Two of the patients with purely motor demyelinating neuropathy were subsequently treated with high dose IVIg (0.4 glkglday for five days) with prompt improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
8

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(128 citation statements)
references
References 20 publications
4
116
0
8
Order By: Relevance
“…The European Federation of Neurological Societies/Peripheral Nerve Society criteria for diagnosing CIDP are based primarily on motor dysfunction 49. The good response of this entity to IVIg50 suggests that these patients may have pronounced inflammatory activity in this subgroup. Therefore of relevance we have shown that patients with motor affection had increased cell counts, particularly dendritic cells without fiber contacts.…”
Section: Discussionmentioning
confidence: 99%
“…The European Federation of Neurological Societies/Peripheral Nerve Society criteria for diagnosing CIDP are based primarily on motor dysfunction 49. The good response of this entity to IVIg50 suggests that these patients may have pronounced inflammatory activity in this subgroup. Therefore of relevance we have shown that patients with motor affection had increased cell counts, particularly dendritic cells without fiber contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the association of this condition with high titres of IgM autoantibodies directed against GM1 ganglioside (Pestronk et al, 1988) and the description of numerous similar cases resulted in this being considered as a separate entity (Nobile-Orazio, 2001). Clarifying the position of LSS among these chronic immune-mediated neuropathies is of therapeutic relevance (Dalakas, 1999), since CIDP shows a beneficial response to plasma exchanges, intravenous immuno globulin (IVIg) and steroids (Hughes et al, 2001;Van Doorn and Garssen, 2002), whereas MMN responds to IVIg (Leger et al, 2001), but not to steroids or plasma exchanges (Pestronk et al, 1988;Donaghy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Steroid therapy is often effective in CIDP, whereas MMN patients do not improve and occasionally even deteriorate with steroid treatment [13,14,15,16,17,18] despite the fact that MMN is pathologically a demyelinating disorder [8]. In addition, plasma exchange is likewise ineffective in MMN [13, 14, 16, 19], although levels of IgM anti-GM1 antibodies are elevated in some patients with MMN [13,14,15,16,17, 20].…”
Section: Discussionmentioning
confidence: 99%